UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PELAJARAN IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PICTURE AND PICTURE DI KELAS VIII A SMP NEGERI 1 SIMPANG KANAN KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR - Julita Nasution; Dr. Gimin '; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study is to investigate the implementation of cooperative learning model Picture and picture to increase learning motivation IPS students of class VIII A SMP Negeri 1 Simpang Kanan. The number of students in this study as many as 20 people. Research conducted in the second half of the 2015/2016 school year in February 2016. Variable measured in this study are the activities of teachers and students with the implementation of cooperative learning model Picture and picture and student motivation. The data collection is done by using observation sheet. These results indicate that the activity of teachers in the application of cooperative learning model Picture and picture in the first cycle of activity Percentage of teachers reached 64.26%. While in the second cycle increased with the percentage of 89.29% both categories all.The activity of the student in the first cycle the percentage of 51.43% on the classification of sufficient whereas in the second cycle student activity increased with increasing percentage of 91.43% with a good classification. The level of student motivation in the first cycle of scores obtained 51.25% is the percentage of students with a good classification. After the second cycle increased with the percentage of 77.72% with a good classification. Based on the results of this study concluded that the implementation of cooperative learning model Picture and picture can increase motivation to learn social science students of class VIII A SMP Negeri 1 Simpang Kanan district. Rokan Hilir.Keywords: Picture and picture and Motivation